All-flexible lithium ion battery based on thermally-etched porous carbon cloth anode and cathode. (August 2016) - Balogun, Muhammad-Sadeeq; Qiu, Weitao; Lyu, Feiyi; Luo, Yang; Meng, Hui; Li, Jiantao; Mai, Wenjie; Mai, Liqiang; Tong, Yexiang
Abstract: Flexible electrode material with high mechanical strength and excellent electrical stability is still a great challenge for the fabrication of highly flexible energy storage devices. Commercial carbon cloth has been long reported as flexible substrate for many electrode materials due to their high mechanical strength and flexibility. However, their application directly as electrode material for flexible lithium ion batteries is yet to be reported. In this paper, commercial carbon cloth was thermally etched and used directly as electrode material in the half-cell and all-flexible full lithium ion batteries. Upon the mass weight and the large diameter of the carbon fiber, the as-prepared free-standing N-doped Porous carbon cloth delivered an initial capacity of 1.75 mA h/cm 2 (190 mA h/g) and capacity up to 1.65 mA h/cm 2 (168 mA h/g) after long electrochemical cycles in the half-cell. The all-flexible device exhibits a high working potential of 3.4 V, remarkable lithium storage performance and excellent flexibility. It also achieves a maximum volumetric energy density of 43 W h/cm 3 at 0.125 mA/cm 2 and power density 800 W/cm 3 at 5.0 mA/cm 2 . The excellent performance can be attributed to N-doped porous surfaces, which provide large surface area for more lithium storage . Graphical abstract: Highlights: The first time Carbon cloth (CC) will be directly used as anode for flexible LIBs. An impressive approach was proposed to improve CC surface area from 7 to 97 m 2 /g. The porous CC displayed excellent lithium storage capacity over the commercial CC. All-flexible lithium ion batteries based on the porous CC were assembled. The device could power different portable devices at the flat and bending positions.